2020
DOI: 10.51253/pafmj.v70i6.4040
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Effect of Hemodialysis on Peripapillary Retinal Nerve Fiber Layer and Macular Thickness

Abstract: Objective: To determine the thicknesses of retinal nerve fiber layer (RNFL) and macula by fourier-domain (FD)optical coherence tomography (OCT) in diabetic patients with end-stage renal failure (ESRF) undergoinghemodialysis. Study Design: Cross-sectional study. Place and Duration of Study: Pakistan Naval Ship, Shifa Karachi, from Jan 2019 to Jul 2019 Methodology: Fifty four patients presenting to nephrology department who met the inclusion criteria wereincluded in the study. Macular and retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The results of our study regarding the increase in RT as a result of a single HD session are consistent with the results of Wang et al, Atilgan et al, and Jabbar et al [7,15,24]. In this study, we also found a statistically significant increase in total pRNFL thickness, which is in agreement with previous studies by Atilgan et al and Jabbar et al in which a statistically significant increase in pRNFL thickness was found after HD session [7,24].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The results of our study regarding the increase in RT as a result of a single HD session are consistent with the results of Wang et al, Atilgan et al, and Jabbar et al [7,15,24]. In this study, we also found a statistically significant increase in total pRNFL thickness, which is in agreement with previous studies by Atilgan et al and Jabbar et al in which a statistically significant increase in pRNFL thickness was found after HD session [7,24].…”
Section: Discussionsupporting
confidence: 93%
“…However, a significant number of studies indicate no effect of an HD session on RT or even a decrease in RT after HD [6,12,13,[16][17][18][19][20][21][22][23]25,26]. The differences may be due to small groups of subjects, methodological differences between studies, differences in the OCT types used, and differences in the groups of subjects themselves, including age, gender, axial length, refraction, or ethnic origin, all of which influence the retinal, GCL and pRNFL thickness [6,7,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]30]. The aetiology of CKD in the studied patients subjected to HD may be of particular importance with respect to differences in the obtained results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations